Superspin glass phase and hierarchy of interactions in multiferroic PbFe1/2Sb1/2O3: an analog of ferroelectric relaxors? - Laguta, V V; Stephanovich, V A; Savinov, M; Marysko, M; Kuzian, R O; Kondakova, I V; Olekhnovich, N M; Pushkarev, A V; Radyush, Yu V; Raevski, I P; Raevskaya, S I; Prosandeev, S A (New journal of physics, 2014)
We have fabricated new perovskite multiferroic PbFe Sb O3 with a high degree (up to 0.9) of chemical ordering and unexpectedly high-temperature magnetic relaxor properties, which can barely be described within concepts of conventional spin glass physics. Notably, we found that the field-temperature phase diagram of this material, in the extremely wide temperature interval, contains the de Almeida-Thouless-type critical line, which has been the subject of long debates regarding its possible experimental realization. We explain our findings by the creation, at high temperatures of not less than 250 K, of giant superspins (SSs), owing, curiously enough, to the antiferromagnetic superexchange interaction. We show that these SSs are capable of strong high-temperature magnetic relaxation in the relaxor phase, down to about 150 K, where they transform into a SS glass phase. On further cooling, the material experiences another striking transition, this time, into an ordinary (single-spin) antiferromagnetic phase. We comprehensively analyze the above complex physical picture in terms of three complimentary theoretical approaches. Namely, the ab initio calculations elucidate the microscopic mechanism of giant SS formation, the high-temperature expansion accounts for the morphology of these clusters, and the random field approach provides the description of disorder-related characteristics.